2011
DOI: 10.1080/14763141.2011.633617
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stride technique and pitch location on slo-pitch batting

Abstract: In slo-pitch softball, the ball is delivered in an arc trajectory with a moderate velocity; hence, batters have time to adjust their stride technique based on the pitched ball location. The purpose of this study was to examine the influence of stride technique and pitched ball location on the mechanics of slo-pitch batting. A two-way ANOVA of two locations of pitch (inside and outside) x three strides (open, parallel, and closed) repeated measure study was conducted in this study. The results showed that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The degree of dissimilarity enabled us to assess if the group mean performance could be generalized to all participants. The rescaled Euclidean distance analysis was the measure of distance between dependent variables for individual performance versus group mean performance, and it ranged between values of 0 for no dissimilarity to a value of 1 for maximum dissimilarity [11]. The results of two-way repeated measured ANOVA (2 locations of pitch x 3 strides) statistical analysis revealed that there was no statistically significant difference in combined percentages of SPC and RSPC between the lower body and trunk segments for the location of pitch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of dissimilarity enabled us to assess if the group mean performance could be generalized to all participants. The rescaled Euclidean distance analysis was the measure of distance between dependent variables for individual performance versus group mean performance, and it ranged between values of 0 for no dissimilarity to a value of 1 for maximum dissimilarity [11]. The results of two-way repeated measured ANOVA (2 locations of pitch x 3 strides) statistical analysis revealed that there was no statistically significant difference in combined percentages of SPC and RSPC between the lower body and trunk segments for the location of pitch.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this study was to examine the slo-pitch hitting movement coordination using the shared positive contribution technique to evaluate players' movement coordination under different task (stride technique) and environmental constraints (location of pitch). Further, each participant's results were compared to the mean to evaluate the degree of dissimilarity between the individuals and the group using a Euclidean distance analysis [11]. These results enabled assessment of whether the group means performance results could be used to generalize to all participants.…”
Section: Res Inves Sports Medmentioning
confidence: 99%
See 1 more Smart Citation